The Comparison Of The Success Rates Of The Prostaglandin E2 (PGE2) Versus Foley Catheter In Females With Postdate Pregnancy - Khan, Qamarunissa Muhabat; Mastoor, Khadija; Javaid, Amna; Raza, Tahira; Ilyas, Sadia; Anjum, Safoora (Journal of Rawalpindi Medical College, 2025)
Objective: Postdate pregnancies, defined as pregnancies that extend beyond the 40th-week gestation, are associated with an increased risk of adverse maternal and fetal outcomes. Consequently, there is a clinical need to manage these pregnancies effectively to prevent complications. Two common methods for inducing postdate pregnancies are the use of Foley catheters and prostaglandins. To determine the success rates of the Foley catheter and prostaglandin E2 (PGE2) in females with postdate pregnancy. Methods: 162 female participants were randomly divided into two groups through the lottery method. Group A utilised a Foley catheter, where after speculum examination, a 16F standard Foley catheter was aseptically inserted above the internal cervical os and inflated with 30ml of sterile water. In Group B, PGE 2 gel was administered, with nulliparous women receiving an initial dose of 2 mg per vaginum (PV) and parous women receiving 1mg PV. The gel was inserted into the posterior vaginal fornix. Success was defined as female giving within 24 hours. The data was analyzed using SPSS version 25. Results: The mean age of patients was 30.35 ± 6.89 years. Success was observed in 87(53.7%) patients, while 75(46.2%) patients did not achieve success. The study findings revealed that success was attained by 30(34.4%) individuals in group A and 57(65.5%) in group B. A statistically significant difference was observed between groups regarding the success of patients. i.e., p-value (<0.05) Conclusion: A study concludes that Prostaglandin E2 (PGE2) showed significantly higher success rates for achieving vaginal delivery within 24.0 hours when compared to Foley catheters in female individuals with postdate pregnancies. Key words: Pregnancy, Prostaglandins E2; Cervical Ripening; Pregnancy Outcome; Labour.